2012
DOI: 10.1007/s10753-012-9567-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lipoxin A4 on Myocardial Ischemia Reperfusion Injury Following Cardiac Arrest in a Rabbit Model

Abstract: In the present study, we investigated the effect of lipoxin A4 on myocardial ischemia-reperfusion injury (IRI) following cardiac arrest (CA) in a rabbit model. Lipoxin A4 is a metabolite of arachidonic acid in the eicosanoid, it is called "brake signal" for its anti-inflammatory activity. Some inflammatory factors (IL-1β, IL-6, TNF-α, and IL-10), NF-κB p65, infarct ratios, apoptotic index, cardiac troponin I (cTnI), hemodynamic and myocardial structures were measured or observed in different groups. Lipoxin A4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Recently, growing evidences demonstrated the efficacy of LXA 4 analogs in treatment of animal arthritis [32], asthma [33], acute lung injury [14], and nephritis [34]. Coupled with previous demonstrations of efficacy of LXA 4 and activation of LXA 4 receptor in treatment of myocardial I/R injury [10], [11], our present results represent useful tools for the development of a new drug for treatment of ischemic heart diseases.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Recently, growing evidences demonstrated the efficacy of LXA 4 analogs in treatment of animal arthritis [32], asthma [33], acute lung injury [14], and nephritis [34]. Coupled with previous demonstrations of efficacy of LXA 4 and activation of LXA 4 receptor in treatment of myocardial I/R injury [10], [11], our present results represent useful tools for the development of a new drug for treatment of ischemic heart diseases.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies attributed the LXA 4 -induced protection on heart I/R injury to the inhibition of neutrophil recruitment and of pro-inflammatory cytokines production [10], [11]. In the present study, we demonstrated for the first time that LXA 4 -induced HO-1 expression participated in the LXA 4 -imparted protection on heart H/R injury.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Although there have been reports showing that LXA 4 treatment was protective in cerebral I/R injury in rats [12] and myocardial I/R injury in mice [47] and rabbits [48], ours is the first study to report a protective effect of LXA 4 preconditioning and postconditioning on myocardial I/R injury in rats. Further studies are needed to optimize the dose, the timing, and the route of administration of LXA 4 .…”
Section: Discussionmentioning
confidence: 74%
“…Our results also suggested that the expression of NF- κ B in damaged testes has been downregulated by the LXA4 pretreatment. Nuclear factor κ B (NF- κ B) is a primary regulator of gene expression for a large number of cytokines and is activated during IRI of testis [26], and LXA4 have been proposed to directly stimulate gene expression of endogenous anti-inflammatory factors by regulating NF- κ B activation [11]. It is suggested that the protective effect of LXA4 in testicular torsion followed IRI was partially due to its anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%